(Study for production of Acetylated Pectin as raw material for Bioplastic Films) - Rienoviar -; Suminar Setiati Achmadi (Warta Industri Hasil Pertanian, 2010)
The study was aim at obtaining the optimal acetylation and activation time for obtaining water insoluble acetylated pectin which would be used for bioplastic material. The activation time for swelling of pectin were 120, 180, and 240 minutes, meanwhile the acetylation time were 60, 90, and 120 minutes. The experiment revealed that the activation time of 180 minutes and acetylation time of 120, 180, and 240 minutes, meanwhile the acetlylation time were of 60, 90, and 120 minutes. The experiment revealed that the activation time of 180 minutes and acetylation time 120 minute, produced water insoluble (hydrophobic) material were diluted in dimethly sulfoxide, and the highest actyl subsitution was 62.9% (wb). Infrared spectrospic analysis indicated that the absoption band of pectin and the acetylated pectin were different at wave number 1743 cm1 of which the ester group of the material can be detected. The analysis of pectin acetate structure by stereophotomicroscope revealed that the highest surface density was resulted from activation time and acetylation time of 120 minutes. Moreover, the best result of the bioplastic sheet of pectin acetate was produced by using pressure of 100 Psi at temperature of 100oC for 5 minutes pressure.